Reset my fight for inclusion and lasting change - Pao, Ellen K. (New York Random House, 2017)
The co-founder of the diversity nonprofit Project Include shares the story behind her landmark 2015 lawsuit against powerhouse venture capitalist firm Kleiner Perkins, exploring what her case and refusal to settle revealed about Silicon Valley discrimination.
Keywords: Sex discrimination in employment--California--Santa Clara Valley (Santa Clara County)